Genetic Testing in Pediatric Left Ventricular Noncompaction. (December 2017) - Miller, Erin M.; Hinton, Robert B.; Czosek, Richard; Lorts, Angela; Parrott, Ashley; Shikany, Amy R.; Ittenbach, Richard F.; Ware, Stephanie M.
Abstract : Background—: Left ventricular noncompaction (LVNC) can occur in isolation or can co-occur with a cardiomyopathy phenotype or cardiovascular malformation. The yield of cardiomyopathy gene panel testing in infants, children, and adolescents with a diagnosis of LVNC is unknown. By characterizing a pediatric population with LVNC, we sought to determine the yield of cardiomyopathy gene panel testing, distinguish the yield of testing for LVNC with or without co-occurring cardiac findings, and define additional factors influencing genetic testing yield. Methods and Results—: One hundred twenty-eight individuals diagnosed with LVNC at ⩽21 years of age were identified, including 59% with idiopathic etiology, 32% with familial disease, and 9% with a syndromic or metabolic diagnosis. Overall, 75 individuals had either cardiomyopathy gene panel (n=65) or known variant testing (n=10). The yield of cardiomyopathy gene panel testing was 9%. The severity of LVNC by imaging criteria was not associated with positive genetic testing, co-occurring cardiac features, etiology, family history, or myocardial dysfunction. Individuals with isolated LVNC were significantly less likely to have a positive genetic testing result compared with those with LVNC and co-occurring cardiomyopathy (0% versus 12%, respectively; P <0.01). Conclusions—: Genetic testing should be considered in individuals with cardiomyopathy co-occurring with LVNC. These data do not suggest an indication for cardiomyopathy gene panel testing in individuals with isolated LVNC in the absence of a family history of cardiomyopathy. Abstract : Supplemental Digital Content is available in the text.